Correlation between Anti-CCP Titer and Body Mass Index Score in Rheumatoid Arthritis Patients in Cipto Mangunkusumo Hospital - Harry Isbagio; Khadijah Fitriah (Indonesian Rheumatology Association, 2018)
Background: Rheumatoid Arthritis (RA) is a chronic systemic inflammation that attacks and damages joints of upper and lower extremities. RA causes morbidity and disability, hence, affects the quality of life. Chronic inflammation, as the disease progressing causes lowering of body mass index in RA patients. Titer of anti-CCP is specific for RA which indicates the progressivity and severity of the disease. Study about anti-CCP titer and body mass index has not been done in Indonesia. Therefore, this study done to understand the correlation between anti-CCP titer and body mass index score in rheumatoid arthritis patients in Cipto Mangunkusumo hospital. Method: The design of this study is cross-sectional study with 42 samples. The data included anti-CCP titer, body weight, height, and body mass index are collected from patients’ medical records. Results: RA patients in Cipto Mangunkusumo hospital in 2012-2016 with negative and positive anti-CCP titer consecutively are 28.6% and 71.4%. The result of this correlation study is p>0.05; r-0.03. Conclusion: In conclusion, there is no correlation between anti-CCP titer and body mass index score in RA patients in Cipto Mangunkusumo hospital Keywords: Anti-CCP; Body Mass Index; Rheumatoid Arthritis